DEVELOPMENT OF SILVOFISHERY IN MANGROVE FOREST, BUDENG VILLAGE - JEMBRANA, BALI - Fitriawati, Ajeng Nurul; Triwanto, Joko; Syarifuddin, Amir (Universitas Muhammadiyah Malang, 2018)
The transfer of mangrove forest into ponds of the silvofishery system becomes one of the solutions in managing the environmental impact. Many areas that have succeeded in developing and highly relevant are applied in other areas such as the area of ponds located in Budeng Village, Jembrana regency, Bali which began to be abandoned threatening to decrease the quality of the environment. The purpose of this research is to study the development of silvofishery system in Budeng village mangrove area.The study was conducted during January - February 2017. The method of plotting plot with combination of stripping path was used to obtain the biotic and abiotic environment of mangrove. Data analysis with qualitative descriptive method according to land criteria for silvofishery development.Biotic and abiotic mangrove environment parameters obtained by pond location in Budeng Village were matched with development table for silvofishery system recommended for silvofishery area. However, it is necessary to stage the addition of mangrove vegetation stand before the silvofishery system is applied because only the vegetation density factor is lacking.